Glottotecnologie didattiche per i migranti L’italiano fra le altre lingue nel progetto L-Pack (Citizenship Language Pack for Migrants in Europe) - Diadori, Pierangela; Tomassetti, Roberto (Incontri. Rivista europea di studi italiani, 2017)
Teaching languages to migrants through ICT L-Pack Project for Italian and other languages (Citizenship Language Pack for Migrants in Europe) The most recent trends in technology and the internet, commonly called Web 2.0., have determined new concepts in teaching and learning that involve autonomy, multimodality and flexibility. New approaches to ‘knowledge by technology’ are changing both teachers’ and learners’ roles, responding to their different aims and needs. At the same time, nearly 4 million people are presently involved in massive migration processes all over Europe, coming either from outside Europe or from another EU member state. The EU policies on migrants state the importance of a basic knowledge of the host country’s language, history and institutions for an effective integration process, and EU governments are expected to contribute to this aim. This paper describes the European Project ‘L-PACK: Citizenship Language Pack For Migrants in Europe’ (2011-2016), whose main aim consisted in developing a series of internet video texts, accompanied with materials and resources to lead adult migrants to A2 level (according to QCER levels scale) in different EU languages. The project has been developed in two main stages. In the first part of the programme, called L-Pack 1, from 2011 to 2013, the languages were Italian, Spanish, German, Lithuanian, Greek and Czech. In the second part, called L-Pack 2 extended, from 2014 to 2016, the project added English and French and was integrated with new resources and tools. The L-PACK course, which consists of 60 short video dialogues from everyday life, supported by comprehension activities and linguistic explanation and rules, is totally free and available through Youtube, Wikibooks and Soundcloud. The dedicated website http://www.l-pack.eu was visited by 120.000 users from 146 countries in the period 2011-2016. L-Pack teaching materials have also been used by teachers in classroom activities. The authors analyze and evaluate the results of the L-Pack Project, from pilot to dissemination, in different learning contexts both in situ and through e-learning. This is carried out on the basis of surveys concerning the project as a whole and in particular its use in Italian language teaching classes for migrants in Italy.